2013
DOI: 10.1016/j.juro.2012.08.084
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Potential of Men with Obstructive Azoospermia Undergoing Percutaneous Sperm Retrieval and Intracytoplasmic Sperm Injection According to the Cause of Obstruction

Abstract: Percutaneous sperm retrieval is an effective method to retrieve sperm in men with obstructive azoospermia irrespective of the cause of obstruction. The chance of achieving a live birth and the profile of neonates born after sperm injection do not seem to be related to the cause of obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 28 publications
0
65
2
Order By: Relevance
“…Meng et al (21) and Aydos et al (22) reported impaired spermatogenesis in some men with CBAVD; animal experiments showed a higher impairment of spermatogenesis with obstruction before maturation of the gonads, compared with obstruction as an adult. In contrast, others demonstrated no effect of the interval since vasectomy on the ICSI outcome in men with obstructive azoospermia after vasectomy (2,(23)(24)(25)(26). This discrepancy could be related to the fact that the etiology of obstruction differs in men who have had a vasectomy, compared with those who have CBAVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meng et al (21) and Aydos et al (22) reported impaired spermatogenesis in some men with CBAVD; animal experiments showed a higher impairment of spermatogenesis with obstruction before maturation of the gonads, compared with obstruction as an adult. In contrast, others demonstrated no effect of the interval since vasectomy on the ICSI outcome in men with obstructive azoospermia after vasectomy (2,(23)(24)(25)(26). This discrepancy could be related to the fact that the etiology of obstruction differs in men who have had a vasectomy, compared with those who have CBAVD.…”
Section: Discussionmentioning
confidence: 99%
“…It is classified into obstructive azoospermia, which is caused by congenital or acquired obstruction, and nonobstructive azoospermia, which is caused by testicular failure (1,2). Azoospermia does not necessarily imply sterility, because many azoospermic men still maintain sperm production at varying levels within their testes (3,4).…”
mentioning
confidence: 99%
“…21 In our series, TESE was done in 33% patients as a rescue procedure after failed PESA whereas, Esteves et al had to revert to rescue procedure in only 17% cases. 22 No difference in fertilization rates was found between the ICSI attempts performed with ejaculated and surgically retrieved spermatozoa in infertile men. There was also no difference in pregnancy outcome between two groups, which is in consensus with many studies.…”
Section: Discussionmentioning
confidence: 93%
“…There was also no difference in pregnancy outcome between two groups, which is in consensus with many studies. 22,23 However, some studies have found lower outcome of ICSI with surgically retrieved sperm vis ejaculated sperms. 24 In our patients, results of ICSI cycles using epididymal and testicular sperm had similar outcomes showing that source of sperm or etiology does not affect sperm injection outcome as also shown in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation